(untitled) (Northern International Medical College Journal, 2024)
Background : Thalassaemia is an important child health issue in Bangladesh and prevention is the key strategy to combat this problem. Teachers can play a significant role in preventing this disease provided they have a good knowledge about the disease. Objective : The Knowledge and practice on thalassaemia among school teachers are unknown. The present study was, therefore, conducted among secondary school teachers of Dhaka City to assess their knowledge and attitude about thalassaemia. Materials & Methods : This cross-sectional study was carried out in 8 secondary schools in Dhaka from January 2018 to June 2018. Out of 24 Govt. Secondary schools of Dhaka city, 8 schools were selected using random table. Four hundred school teachers from the 8 government schools were then selected using systematic sampling method. A semi structured questionnaire was used to evaluate knowledge of the respondents about thalassaemia. The test statistics used to analyze the data were descriptive statistics. The questionnaire also assessed preventive strategy and difference in attitude towards thalassaemia. Result : The majority of the secondary school teachers are informed about thalassaemia, but their knowledge is inadequate regarding occurrence, nature and prognosis of thalassaemia. Among the respondents 6% had a good level of knowledge, 20% had average and 74% had poor level of knowledge. Regarding views on prevention, 16.5% thought the necessity of prenatal diagnosis of the carrier couples and 24.4% agreed that thalassaemia carriers should not marry each other. About 32.5% of the respondents were in agreement that premarital screening is essential for the prevention of thalassaemia to next generation. Conclusion : Most of the secondary school teachers have poor knowledge in general aspects and preventive measures of thalassaemia. Majority of the teachers did not have positive attitude towards premarital screening for thalassaemia carrier, however majority of them showed positive attitude towards creation of an academically friendly environment for the thalassaemic patients. Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 568-573